THE ROLE OF DIGITAL MARKETING IN COMMUNITY ENGAGEMENT MODERATED BY BRAND AWARENESS (A STUDY OF CONSUMERS OF BEEBOT AUTOMOTIVE PRODUCTS ON THE TIKTOK CAR COMMUNITY PLATFORM) - Jochanan Benaya Lumban Tobing; Popy Rufaidah (SOSIOEDUKASI, 2025)
The incredible pace of digital technology progress has changed how business' build the relationships with consumers- through social media interactions and online communities. In the automotive aftermarket, digital marketing is an especially important tool for businesses that want to build stronger community connections and increase their brand visibility. This study delves into the impact of digital marketing on community engagement, specifically looking at Beebot Automotive product users on TikTok and the Indonesian automotive community. It also examines the moderating variable of brand awareness in this context. A quantitative explanatory approach was applied using an online survey method targeting members of car communities who actively. use Beebot products. Data were collected using a Likert-scale questionnaire developed from theoretical indicators proposed by recent studies. A Structural Equation Modelling (SEM) using Partial Least Squares (PLS) analysis will be performed on the data in order to examine the direct and moderating effects among the variables. The results should help advance digital marketing theory while also giving businesses in the car sector actionable advice on how to boost community participation via digital means and solidify their brand's position in a crowded marketplace.